Uczeń zdolny w perspektywie dyskursu produkcyjnego. Część II: Świat szkoły - Astrid Męczkowska-Christiansen; Kamila Zdanowicz-Kucharczyk (Problemy Wczesnej Edukacji)
The paper is a continuation and, at the same time, an empirical illustration of considerations regarding the production discourse of a talented student with neoliberal provenance (Męczkowska-Christiansen 2018). The presented analyses are embedded in the perspective of critical discourse analysis and include insight into selected school practices of meeting the challenges of gifted education. They used a variety of data, including document analysis and narrative interviews. As a result of the analyses, the school strategies for “dealing” with talented students were highlighted, emphasizing their exploitative dimension.